2013
DOI: 10.1002/masy.201350507
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrillar Polymer‐Polymer Composites: Effect of Reinforcement Orientation on the Mechanical Properties

Abstract: Summary In‐situ poly (ethylene terephthalate) (PET) nanofibrils were created by drawing of melt blended polypropylene and PET. The drawn blend was used to prepare polymer‐polymer nanofibrillar composites (NFCs), in order to compare the effect of different fibril orientations on the mechanical properties. The resulting composites showed excellent improvements in stiffness of 116% vs. the isotropic PP matrix for uniaxial NFCs, with the highest recorded modulus of 4.16 GPa for a uniaxial NFC sample, and 3.41 GPa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…It is fortunate that in situ nanofibrillation has been realized in various blend systems or single-polymer composites. However, we provide first observations for the formation of unique PBS nanofibrils. Generally, some specific blend systems constituting a matrix component with a low processing temperature and a fibrous component offering high strength and modulus are employed to fabricate in situ fibrillar composites. ,, The present attempts fail to provide an available inroad to introduce nanofibrillar phase into the strong but brittle matrix like our proposal.…”
Section: Resultsmentioning
confidence: 86%
“…It is fortunate that in situ nanofibrillation has been realized in various blend systems or single-polymer composites. However, we provide first observations for the formation of unique PBS nanofibrils. Generally, some specific blend systems constituting a matrix component with a low processing temperature and a fibrous component offering high strength and modulus are employed to fabricate in situ fibrillar composites. ,, The present attempts fail to provide an available inroad to introduce nanofibrillar phase into the strong but brittle matrix like our proposal.…”
Section: Resultsmentioning
confidence: 86%
“…McCardle and co-workers [151,152] have investigated the orientation of the fibrils on the mechanical properties. They have reported achievement of the highest values for the mechanical properties in the case of uniaxially oriented MFCs, but in crossply MFCs, significant improvements were detected as well.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…[20] It should be mentioned that in these [10][11][12][13][14][15][16][17][18][19] and other similar studies, highly oriented textile filaments or strips have been used as starting materials for manufacturing of SPCs. Only very recently [20][21][22][23][24][25][26][27][28][29][30][31][32] has it been demonstrated that for the same purpose polymer-based microfibrils (diameters of one or a couple of mm) or nanofibrils (diameters between 50 and 250 nm) could be used.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of this study is applying the experience gained in developing the MFCs [1] and SPCs [20][21][22][23][24][25][26][27][28][29][30][31][32] to isolate microfibrils of poly(butylene terephthalate) loaded with MWCNTs from a blend and to use them to prepare MF-SPCs. These SPCs are characterized mechanically and electrically.…”
Section: Introductionmentioning
confidence: 99%